(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Obstructive jaundice is frequently encountered worldwide including Bangladesh. Therapeutic Endoscopic Retrograde Cholangiopancreatography (ERCP) is one of the procedures to manage obstructive jaundice. Objectives: To ascertain the outcome of obstructive jaundice patients who underwent ERCP. Materials and Methods: It was a hospital based cross sectional observational study, carried out in Gastroenterology Department of Combined Military Hospital (CMH) Dhaka from May 2017 to May 2019. Total 200 patients were included in the study. Verbal consents were taken from patients. Data were collected with a checklist and analyzed by using SPSS 20. Results: Total 200 patients’ mean age±SD was 56.5±14.5 years with range 21 to 92 years and majority were 41 to 60 years 80(40%) followed by 61 to 80 years 78(39%). Etiology of obstructive jaundice were, benign 137(68.5%) and malignant 63(31.5%). Among the benign: 69(34.5%) were choledocholithiasis, 45(22.5%) biliary stricture, 20(10.0%) papillary stenosis and 3(1.5%) biliary warms. Among the malignant: 24(12.0%) were distal cholangiocarcinoma, 21(10.5%) periampullary tumors, 10(5.0%) Klatskin tumor, 4(2.0%) carcinoma head of pancreas, and 4(2.0%) other malignancy. Mean serum bilirubin level 17.6 mg/dl with minimum 0.6mg/dl, maximum 41.3mg/dl; mean alkaline phosphatase (ALP) level 351.4U/L with minimum 111U/L and maximum 1262U/L; mean alanine aminotransferase (ALT) level 118.8 U/L with minimum 28 U/L, maximum 521 U/L; ERCP were successfully done in 188(94.0%) patients with single attempt 171 (85.5%), repeated sessions 17(8.5%) and 12(6.0%) patients unsuccessful ERCP; complications occurred in 17(8.5%)patients, of whom post-ERCP pancreatitis 9(4.5%) and post procedure cholangitis 4(2.0%)patients. Conclusion: Benign etiologies of obstructive jaundice were more common than malignant one. Both benign and malignant etiology of obstructive jaundice can be successfully managed with ERCP with few complications. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 27-30